Peran Ibu dalam Mengajarkan Moderasi Beragama pada Anak di Masa Pandemi COVID 19 - Heny Kusmawati; Anista Ika Surachman (EL-TARBAWI, 2021)
Starting from the hadith narrated by narrated by Imam Muslim whichmeans: "every human being is born upon fitrah. His parents made himJewish, Christian or Majusi." From this hadith, it is clear that parents havebig role in shaping children religiosity. Thus, the obligation of parents is tomake children have religious maturity by doing religious moderation so thatchildren develop an attitude of respect for other religions. Moreover,education during the Covid-19 pandemic which is more conducted at homemakes the mother figure a determinant of the success of teaching religiousmoderation in children. The purpose of writing this article is to describemothers and how to teach religious moderation to children during the Covid-19 pandemic. The research is qualitative research with grounded theorymethod, it used interview in collecting data with the help from relatedwritten references on the theory of religious moderation. The results of thisarticle concluded 1) the urgency to prevent children from radical literacy incyberspace, and 2) the stages of teaching Pancasila values that are inaccordance with religious moderation in the neighborhood.Keywords: Mother; Education; Moderation; Religion